2022
DOI: 10.1155/2022/6253978
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD44 and EGFR Dual-Targeted Solid Lipid Nanoparticles for Delivery of Doxorubicin to Triple-Negative Breast Cancer Cell Line: Preparation, Statistical Optimization, and In Vitro Characterization

Abstract: Background. Despite being more aggressive than other types of breast cancer, there is no suitable treatment for triple-negative breast cancer (TNBC). Here, we designed doxorubicin-containing solid lipid nanoparticles (SLNs) decorated with anti-EGFR/CD44 dual-RNA aptamers, which are overexpressed in TNBC. For more efficiency in the nuclear delivery of doxorubicin, dexamethasone (Dexa) was chemically attached to the surface of nanoparticles. Methods. To prepare the cationic SLNs, 6-lauroxyhexyl BOC-ornithine (LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…TNBC is an aggressive and fatal breast tumor and poor prognosis and metastasis occur more in this subtype than other subtypes even though the TNBC only contributes 15–20 % of breast cancer cell types. The findings demonstrated that the two‐aptamer‐containing system is a promising strategy for combination therapy [92] . Figure 6 is the schematic representation of a DOX encapsulated in surface modified solid lipid nanoparticles with dual targeting EGFR and CD44 RNA aptamers”.…”
Section: Aptamers In Targeted Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…TNBC is an aggressive and fatal breast tumor and poor prognosis and metastasis occur more in this subtype than other subtypes even though the TNBC only contributes 15–20 % of breast cancer cell types. The findings demonstrated that the two‐aptamer‐containing system is a promising strategy for combination therapy [92] . Figure 6 is the schematic representation of a DOX encapsulated in surface modified solid lipid nanoparticles with dual targeting EGFR and CD44 RNA aptamers”.…”
Section: Aptamers In Targeted Drug Deliverymentioning
confidence: 99%
“…The findings demonstrated that the two-aptamer-containing system is a promising strategy for combination therapy. [92] Figure 6 is the schematic representation of a DOX encapsulated in surface modified solid lipid nanoparticles with dual targeting EGFR and CD44 RNA aptamers".…”
Section: Aptamers In Targeted Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone was chemically attached to the surface of the nanoparticles for more efficient delivery of doxorubicin to the nucleus of MDA-MB-468 cells. It was found that this designed nanoparticle was more effective than its components alone in inhibiting MDA-MB-468 cell proliferation [ 94 ].…”
Section: Dna-based Materialsmentioning
confidence: 99%
“…According to the recent statistics of the International Agency for Research on Cancer, breast cancer has become the most diagnosed cancer in both sexes [87]. Much attention has been paid to develop novel materials for breast cancer treatment [88][89][90][91]. Recently, increasing number of studies have shown the efficiency of single-atom nanozymes in breast cancer therapy.…”
Section: Breast Cancer Treatmentmentioning
confidence: 99%